2023
DOI: 10.1093/cid/ciad132
|View full text |Cite
|
Sign up to set email alerts
|

Programmatic Effectiveness of a Pediatric Typhoid Conjugate Vaccine Campaign in Navi Mumbai, India

Abstract: Background The WHO recommends vaccines for prevention and control of typhoid fever, especially where antimicrobial-resistant typhoid circulates. In 2018 the Navi Mumbai Municipal Corporation (NMMC), implemented a TCV campaign. The campaign targeted all children aged 9-months through 14-years within NMMC boundaries (∼320,000 children) over 2 vaccination phases. The phase 1 campaign occurred from July 14-August 25, 2018 (71% coverage, ∼113,420 children). We evaluated the phase 1 campaign’s prog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Hoffman et al, 2023 [35] Prospective blood culture-based surveillance study was conducted in six hospitals in Navi Mumbai, India. 81 typhoid cases and 238 matched controls were included.…”
Section: Author Study Design and Methods Key Findingsmentioning
confidence: 99%
“…Hoffman et al, 2023 [35] Prospective blood culture-based surveillance study was conducted in six hospitals in Navi Mumbai, India. 81 typhoid cases and 238 matched controls were included.…”
Section: Author Study Design and Methods Key Findingsmentioning
confidence: 99%
“…This single-dose conjugate vaccine provides immunity against Salmonella Typhi, the causative agent of typhoid fever, and has been recommended by the Strategic Advisory Group of Experts for routine use in countries where typhoid fever is endemic [4,5]. Studies from Nepal, Bangladesh, India, Pakistan and Malawi have shown high efficacy of Vi-TT vaccine in preventing typhoid fever [6][7][8][9][10]. In 2020 a second TCV, Vi-diphtheria toxin (Vi-CRM 197 ) vaccine, was prequalified by WHO and clinical trials are ongoing [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, effectiveness studies from Pakistan and India showed high levels of protection from a single dose of TCV, including against XDR S. Typhi. 23 , 24 As typhoid endemic countries begin to incorporate TCV into their national immunization programs, studies that report longitudinal incidence data – such as this one from Ng’eno et al. – will be essential to understand the impact of vaccination on typhoid incidence and S. Typhi resistance.…”
mentioning
confidence: 99%